The Effect of Progressive Muscle Relaxation Therapy on Anxiety in Hypertension Patients - Nasihin, Nasihin; Pertiwi, Diah Ayu; Khayan, Khayan; Puspita, Widyana Lakshmi; Hanif, Muhammad Ifham (JURNAL INFO KESEHATAN, 2022)
Anxiety is a condition in which an individual experiences a concern about something that is not certain to happen, even some people experiencing anxiety but do not understand the specific cause of the anxiety source they feel. Anxiety problems, which are common in people, can be treated non-pharmacologically with deep muscle relaxation techniques, which do not require guided imagination or cause side effects in patients undergoing progressive muscle relaxation therapy. The objective of this study is to identify how progressive muscle relaxation techniques affected the anxiety levels of hypertension patients at the Kedaung Wetan Public Health Center. The study was conducted to determine if there was a difference in the level of anxiety experienced by hypertensive patients before and after receiving progressive muscle relaxation therapy. The design in this study employed a quasi-experimental pre-post-test with a control group with a progressive muscle relaxation therapy intervention. Result: there is a significant relationship between the period of occurrence of hypertension with anxiety experienced by respondents. Anxiety in hypertensive patients is more prevalent in those who are unfamiliar with hypertension. Thus, anxiety can arise from a sense of concern and fear of more serious complications which occur from the hypertension they are experiencing. The experimental group who received treatment in the form of progressive muscle relaxation therapy had a lower level of anxiety than the control group at the Kedaung Wetan Public Health Center in Tangerang City, with a p-value of 0.000.